2023
DOI: 10.47197/retos.v51.100564
|View full text |Cite
|
Sign up to set email alerts
|

Sensor-based Reactive Agility Measurement Tool for Net Game Group Sports: Content Validity

Abdul Alim,
Tomoliyus Tomoliyus,
Ucok Hasian Refiater
et al.

Abstract: It is challenging to develop a measurement of Reactive Agility because the latter is one of the physical components that is highly influenced by internal and external factors. It is thus difficult to perform related measurements due to uncertainties in open game conditions, specifically in the net game group. The purpose of this research is to validate the content of a sensor-based Reactive Agility measurement tool in net game group sports. In terms of the research method, the researchers used a mixed-method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The first analysis process found that there was no Y form of agility in badminton. It was then discovered that the agility test model was Y-shaped with variations in path or slope angle Alim et al, 2024). In the age classification, search results found that the beginning of a career in badminton starts from the age of 15 (Williyanto et al, 2021); (Kusnadi et al, 2022); (Rodríguez et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first analysis process found that there was no Y form of agility in badminton. It was then discovered that the agility test model was Y-shaped with variations in path or slope angle Alim et al, 2024). In the age classification, search results found that the beginning of a career in badminton starts from the age of 15 (Williyanto et al, 2021); (Kusnadi et al, 2022); (Rodríguez et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Then the development of the Y form of agility test was also developed for field tennis through validity and reliability tests (W. . This research method is to test validity and reliability, the validity test is carried out by experts and coaches in the field of badminton, then the reliability test is carried out by badminton athletes directly (Alim et al, 2024). With a high value of validity and reliability, it is expected that it can be used repeatedly and have a high level of test reliability (Yudhistira & Tomoliyus, 2020); (Qowiyyuridho et al, 2021); (Yudhistira et al, 2021)).…”
Section: Introductionmentioning
confidence: 99%